The beliefs about race and culture operating in our discipline strategies: a commentary. Issue 3 (3rd May 2021) - Fergus, Edward
Abstract: The prevalence of racial disparities in discipline outcomes continues despite a prominence of new strategies and research. When implemented with fidelity, PBIS (Positive Behavior Interventions and Supports) is shown to contribute to reductions in school suspension, expulsion, and other positive educational outcomes. Despite its promise for making school discipline more efficient and less exclusionary, PBIS in some schools struggles to address disproportionate patterns of exclusion and office referrals. This commentary offers the use of critical race theory framing as a way to understand how teachers' beliefs about race and culture operate within their personalized lives and transfer themselves within the schooling environment.